Exploiting guava leaf extract as an alternative natural reagent for flow injection determination of iron - Settheeworrarit T. (2014)
Guava leaf extract is utilized as an alternative natural reagent for quantification of iron. The flow injection technique enables the use of the extract in acetate buffer solution without the need of further purification. Some properties of the extract such as its stability and ability to form a colored complex with iron were studied. The proposed system is an environmentally friendly method for determination of iron with less toxic chemical wastes. © 2005 Elsevier B.V. All rights reserved.